Pembrolizumab in the treatment of non-small cell lung cancer—experiences from clinical practice - Lackovic, Lora Novakovic; Tomic, Milica Srecic; Novakovic, Marko; Turic, Mirko; Kajkut, Aleksandra; Macinkovic, Teodora; Stanetic, Mirko; Glamocak, Ranko (Frontiers in Medicine, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have become the standard first-line treatment for patients with advanced or metastatic non-small cell lung cancer (NSCLC) without targetable mutations. This study aimed to assess real-world outcomes of pembrolizumab monotherapy in patients with high PD-L1 expression (≥50%) and compare them with results from the KEYNOTE-024 clinical trial.MethodsThis retrospective study included patients with advanced or metastatic NSCLC treated with pembrolizumab as first-line therapy at the Clinic for Pulmonary Diseases, University Clinical Center of Republika Srpska, between January 2018 and December 2022. Clinical and pathological data were collected from medical records and analyzed using descriptive and inferential statistical methods.ResultsThe cohort included 46 patients with a median age of 64 years; 56.5% were aged ≥65, 73.9% were male, 76% were smokers, and 72% had an ECOG performance status of 1. Adenocarcinoma (AC) and squamous cell carcinoma (SCC) were diagnosed in 50 and 46% of cases, respectively, while 70% had metastatic disease and 15% had brain metastases. The two-year objective response rate (ORR) was 72.2%, lower than the 85.7% reported in KEYNOTE-024, possibly due to differences in PD-L1 assay (SP263 vs. 22C3) and patient selection. Despite this, the median overall survival (OS) was 36 months—higher than in the trial. One-, two-, and three-year survival rates were 57.9, 53.5, and 42.8%, respectively.ConclusionOur findings confirm the clinical benefit of pembrolizumab in a real-world setting, despite lower ORR compared to clinical trial data. However, the prognosis remains guarded due to the advanced stage and comorbidities of the population. Further investigation is warranted to optimize patient selection and treatment strategies.